High-strength corrosion-resistant Ti-Al-Mo-Cr-Nb series titanium alloy and preparation method thereof

By adjusting the composition of Ti-Al-Mo-Cr-Nb-based titanium alloy and using specific heat treatment processes to form an isometric or bistate structure, the problems of insufficient strong plasticity matching and insufficient corrosion resistance of β-titanium alloy are solved, and the combination of high strength and good corrosion resistance is achieved, which is suitable for high-performance applications.

CN119614944APending Publication Date: 2025-03-14NANJING UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411881771.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing β-titanium alloys are difficult to balance between mechanical properties and corrosion resistance, and the strong plasticity matching and corrosion resistance are insufficient, which limits its wide application in aerospace, marine ships and petrochemical industries.

Method used

By adjusting the chemical composition of Ti-Al-Mo-Cr-Nb-based titanium alloy and adopting specific heat treatment processes, isometric or bistate structures are formed, including vacuum magnetic levitation induction furnace smelting, homogenizing heat treatment, beta-billed forging, multi-pass rolling, solid solution treatment and aging treatment.

Benefits of technology

The combination of high strength and good ductility is achieved, which improves the reliability of the material under high stress environments and significantly improves its corrosion resistance, making it suitable for high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614944A_ABST
    Figure CN119614944A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength corrosion-resistant Ti-Al-Mo-Cr-Nb series titanium alloy and a preparation method of the high-strength corrosion-resistant Ti-Al-Mo-Cr-Nb series titanium alloy. 6%-7% of Mo; 2%-3% of Cr; 2%-5% of Nb, and the balance Ti and inevitable impurities. The method comprises the following steps: burdening, smelting, homogenizing heat treatment, beta forging forming, multi-pass rolling forming of a forging stock in an alpha + beta two-phase region, and solid solution and aging heat treatment. The tensile strength of the prepared titanium alloy can reach 1162-1368 MPa, and the ductility of the titanium alloy ranges from 6.6% to 13.7%. The excellent strength and plasticity matching and the wide mechanical property regulation and control interval are shown. Meanwhile, the prepared titanium alloy also has excellent corrosion resistance, so that the light high-strength corrosion-resistant titanium alloy has great potential application value in the fields of aerospace, marine ships, petrochemical engineering and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a high-strength and corrosion-resistant Ti-Al-Mo-Cr-Nb titanium alloy used in the fields of aerospace, marine ships, petrochemical industry, and the like, and a preparation method thereof. Background Art

[0002] Titanium alloys are widely used in aerospace, marine, petrochemical and other fields due to their light weight, high strength, good corrosion resistance and oxidation resistance. In particular, β-type titanium alloys have attracted much attention due to their excellent mechanical properties and processing properties. However, when the strength of β-titanium alloys exceeds 1100MPa, their plasticity and corrosion resistance decrease significantly. The existing β-titanium alloys still have insufficient strength-plasticity matching and corrosion resistance in certain application environments, which limits their wide application.

[0003] Traditional β-titanium alloys usually contain elements such as Ti, Al, Mo, and Nb. By adjusting the proportions of these elements, the mechanical properties and corrosion resistance of the alloy can be improved. However, existing β-titanium alloys often find it difficult to strike a balance between mechanical properties and corrosion resistance. For example, in aerospace applications, titanium alloys need to have high strength and good fatigue resistance; in marine engineering, titanium alloys need to have excellent corrosion resistance to cope with the corrosive environment in seawater. Although some progress has been made by adjusting the alloy composition and optimizing the heat treatment process, the existing technology still has some limitations:

[0004] Insufficient strength-ductility matching: Although existing β-titanium alloys have high tensile strength, their elongation is generally low, which makes them prone to brittle fracture under high stress environments. This brittle fracture not only affects the service life of the material, but may also cause catastrophic accidents.

[0005] Insufficient corrosion resistance: In certain corrosive environments, such as marine environments and acidic media, existing titanium alloys are prone to corrosion, affecting their service life and safety. Especially in marine environments, the presence of chloride ions can cause pitting and crevice corrosion of titanium alloys, seriously affecting their durability.

[0006] In order to overcome the above problems, researchers have proposed a series of improvement measures. For example, by adjusting the alloy composition, specific elements are introduced to improve the mechanical properties and corrosion resistance of the alloy. Common improvement measures include adding molybdenum Mo and Cr to improve the strength and hardness of the alloy, and adding niobium Nb to improve the plasticity and toughness of the alloy. In addition, multi-pass forging and solid solution aging treatment are used to refine the grain structure and promote the formation of precipitation phases, thereby improving the comprehensive performance of the alloy. Although these methods have improved the performance of titanium alloys to a certain extent, there are still some limitations, such as limited composition range, high process complexity, and insufficient corrosion resistance. Summary of the invention

[0007] The purpose of the present invention is to provide a high-strength and corrosion-resistant Ti-Al-Mo-Cr-Nb titanium alloy and a preparation method thereof. Through specific alloy composition and processing technology, the alloy has excellent strength-plasticity matching and corrosion resistance, thereby meeting the needs of high-performance applications.

[0008] The technical solution to achieve the purpose of the present invention is achieved as follows:

[0009] In the first aspect, the present invention provides a high-strength and corrosion-resistant Ti-Al-Mo-Cr-Nb titanium alloy, whose chemical composition, by weight percentage, is 3% to 4% Al, 6% to 7% Mo, 2% to 3% Cr, and 2% to 5% Nb; the remainder is Ti and unavoidable impurities.

[0010] Preferably, the titanium alloy has an equiaxed or bimodal structure.

[0011] In a second aspect, the present invention provides a method for preparing a Ti-Al-Mo-Cr-Nb titanium alloy, comprising the following steps:

[0012] The first step: batching, using block or granular high-purity metals of Ti, Al, Mo, Cr, and Nb as raw materials, accurately batching and mixing according to the required alloy composition;

[0013] The second step: melting, using a vacuum magnetic levitation induction furnace to melt the alloy under argon protection to ensure uniform alloy composition;

[0014] Step 3: Homogenization heat treatment: homogenization heat treatment is performed on the smelted ingot, heating it to 1100℃~1150℃, keeping it warm for 2 hours, and then taking it out and air cooling it;

[0015] Step 4: β-opening forging, heating to 950℃~1100℃, and performing β-opening forging on the ingot;

[0016] Step 5: Multi-pass rolling, in which the forging blank is formed by multi-pass rolling at the temperature of α+β phase region, i.e., 780℃~840℃;

[0017] Step 6: Two-phase solid solution treatment: the rolled alloy is subjected to solid solution treatment, heated to 800℃~830℃ and maintained for 1~2 hours, and then taken out of the furnace and air cooled;

[0018] Step 7: Aging treatment: The alloy after solution treatment is aged at 500℃~600℃ for 4~8 hours, and then air-cooled after being taken out of the furnace.

[0019] Preferably, the vacuum suspension induction melting is repeated at least three times to ensure uniform alloy composition.

[0020] Preferably, the homogenization heat treatment temperature is 1100°C and the time is 2 hours.

[0021] Preferably, the β-forging of the ingot means performing three forging passes at 950°C to 1100°C, with the first pass temperature being 1100°C, the second pass temperature being 1000°C, and the third pass temperature being 950°C.

[0022] Preferably, the forging blank is subjected to multi-pass rolling forming at the temperature of the α+β two-phase region, the multi-pass rolling temperature is 810° C., and the total deformation is 60%.

[0023] Preferably, the solution treatment temperature is 820°C and the holding time is 1.5 hours.

[0024] Preferably, the aging treatment temperature is 550°C and the holding time is 8 hours.

[0025] The mechanical properties of the titanium alloy after the above treatment are as follows: tensile strength is 1162-1368 MPa, and elongation is 6.6-13.7%.

[0026] The corrosion performance of the alloy was tested by electrochemical tests in a simulated corrosion environment as follows: the corrosion potential was -0.422 to -0.281 V vs. SCE, and the self-corrosion current density was 2.738 × 10 -8 ~3.671×10 -8 A / cm 2 .

[0027] Compared with the prior art, the present invention has the following beneficial effects: the high-strength and corrosion-resistant Ti-Al-Mo-Cr-Nb titanium alloy provided by the present invention not only has excellent mechanical properties, but also exhibits good corrosion resistance, and is particularly suitable for applications in aerospace, marine ships, petrochemicals and other fields. Specific advantages include:

[0028] (1) Through specific alloy composition and heat treatment process, a combination of high strength and good ductility is achieved, which improves the reliability of the material in high stress environments.

[0029] (2) Through optimized composition, heat treatment and processing, a fine and uniform microstructure is formed, which makes the alloy have excellent corrosion resistance and contributes to its stability in corrosive environments.

[0030] (3) This alloy is not only suitable for aerospace, marine and petrochemical industries, but can also be used in other applications that require high strength and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention is described in detail below with reference to the accompanying drawings.

[0032] Figure 1These are the microstructure diagrams of alloy No. 6 at different magnifications.

[0033] Figure 2 These are the microstructure diagrams of alloy No. 7 at different magnifications.

[0034] Figure 3 These are the microstructure diagrams of alloy No. 8 at different magnifications.

[0035] Figure 4 This is the room temperature tensile stress-strain curve of alloys 6 to 8. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.

[0037] The present invention aims to provide a high-strength and corrosion-resistant Ti-Al-Mo-Cr-Nb titanium alloy and a preparation method thereof. Through specific alloy components and optimized processing technology, the present invention solves the problems of insufficient strength-plasticity matching and insufficient corrosion resistance in the prior art, thereby meeting the needs of high-performance applications. Specifically, the main components of the titanium alloy described in the present invention are Ti-3%~4%Al-6%~7%Mo-2%~3%Cr-2%~5%Nb (weight percentage), and the alloy is smelted in a vacuum magnetic levitation induction furnace, followed by homogenization heat treatment, β forging, multi-pass rolling, solution treatment and aging treatment, and finally a titanium alloy with excellent strength-plasticity matching and corrosion resistance is obtained.

[0038] Example

[0039] In order to screen out the appropriate composition ratio, a series of alloys were pre-smelted and processed through the steps of homogenization at 1100℃ for 2h, β-open forging, multi-pass rolling in the two-phase zone, and solid solution + aging in the two-phase zone. The specific alloy composition and preparation process parameters are shown in Table 1.

[0040] Table 1: Alloys with different compositions and their preparation process parameters

[0041]

[0042] The preparation of the above alloys No. 1 to No. 11 is achieved by the following steps:

[0043] (1) Batching: Use high-purity metals such as Ti, Al, Mo, Cr, and Nb in block or granular form as raw materials, and accurately batch and mix them evenly according to the required alloy composition.

[0044] (2) Melting: The alloy is melted in a vacuum magnetic levitation induction furnace under argon protection for at least 3 times to ensure uniform alloy composition.

[0045] (3) Homogenization heat treatment: The smelted ingot is subjected to homogenization heat treatment at a temperature of 1100°C for 2 hours, followed by air cooling.

[0046] (4) β-forging: Except for alloy No. 9, all other alloys were subjected to β-forging treatment, with the first pass temperature being 1100°C, the second pass being 1000°C, and the third pass being 950°C.

[0047] (5) Multi-pass rolling: The forged titanium alloy forging billet is subjected to multi-pass hot rolling on a rolling mill. The rolling temperature of alloy No. 10 is 900°C, and the rolling temperature of the other alloys is 810°C. The total deformation of all alloys is 60%.

[0048] (6) Solution treatment: The rolled alloys were subjected to solution treatment. The solution temperature of alloy No. 11 was 900°C, and the solution treatment temperature of the other alloys was 820°C. The holding time for all alloys was 1.5 hours, followed by air cooling.

[0049] (7) Aging treatment: The alloy after solution treatment is subjected to aging treatment at a temperature of 550°C for 8 hours, followed by air cooling.

[0050] The mechanical properties of alloys 1 to 11 were tested, and the results are shown in Table 2.

[0051] Table 2: Comparison of mechanical properties of alloys with different compositions

[0052]

[0053] As can be seen from Table 2, the strength-plasticity matching of Ti-Al-Mo-Cr-Nb series titanium alloys No. 6 to 8 treated with steps such as homogenization at 1100℃ for 2h, β-opening forging, multi-pass rolling in the two-phase region, solid solution in the two-phase region + aging is better than that of other alloys, and their tensile strengths are 1162MPa, 1245 and 1368MPa, respectively, and their elongations are 13.7%, 10.2% and 6.6%, respectively, showing high strength and considerable plasticity, which also shows that the Ti-Al-Mo-Cr-Nb series titanium alloy of the present invention has a wide performance control range. The strength-plasticity matching of the remaining alloys is insufficient, and the following index requirements are not achieved: when the tensile strength is at the level of 1150MPa, the elongation is not less than 13.5%; when the strength is at the level of 1200MPa, the elongation is not less than 10%; when the strength is at the level of 1350MPa, the elongation is not less than 6.5%.

[0054] Among them, the tensile strength of alloy No. 9, which has the same composition as alloy No. 6 but has not been β-forged, is 1112MPa and the elongation is 11%, both lower than alloy No. 6, and the strength-plasticity matching of not less than 13.5% at the strength level of 1150MPa is not achieved. This shows that the β-forging forming process is indispensable, and the three-pass β-forging forming refines the alloy grains, provides good organizational conditions for rolling forming, and is conducive to the improvement of the strength-plasticity matching of the alloy.

[0055] Alloy No. 10, which has the same composition as Alloy No. 7 but different rolling process parameters, has a tensile strength of 1390MPa and an elongation of 4.5%, which fails to achieve the strong-plastic matching of an elongation of not less than 6.5% at a strength level of 1350MPa. This is because the rolling temperature in the β single-phase region is high, which cannot induce the formation of the primary α phase. After solution aging, only the secondary α phase precipitates, resulting in insufficient plastic deformation capacity of Alloy No. 10.

[0056] Alloy No. 11, which has the same composition as Alloy No. 8 but different heat treatment parameters, has a tensile strength of 1448MPa and an elongation of 3.4%, which fails to achieve the strong-plastic matching of an elongation of not less than 6.5% at a strength level of 1350MPa. This is because the solid solution in the β single-phase region causes the primary α phase to be completely dissolved in the matrix, resulting in the precipitation of a large amount of secondary α phase during the aging process, which seriously hinders dislocation slip, resulting in high strength of Alloy No. 11, but severe loss of plasticity.

[0057] The microstructure of alloys 6 to 8 with excellent strength-ductility matching was observed.

[0058] Figure 1 This is the SEM microstructure diagram of alloy No. 6. It can be seen that the alloy presents a typical equiaxed structure. The primary α phase content is relatively high, accounting for about 48%. The primary α phase can store dislocations well, which is conducive to plastic deformation. The fine secondary α phase inside the matrix can hinder dislocations and improve the strength of the alloy, ultimately making the alloy have excellent strength-plasticity matching.

[0059] Figure 2 This is the SEM microstructure diagram of alloy No. 7. It can be seen that the alloy presents a typical dual-state structure. The primary α phase content accounts for about 30%. A certain amount of primary α phase ensures the plastic deformation ability of the alloy, so that the alloy has a tensile strength of 1245MPa while still maintaining an elongation of 10.2%.

[0060] Figure 3 This is the SEM microstructure diagram of alloy No. 8. It can be seen that the content of primary α phase in this alloy is less than that in alloys No. 6 and 7, accounting for about 12%, and the content of secondary α phase is higher. Therefore, alloy No. 8 has higher strength, but still maintains a considerable elongation at this strength level.

[0061] Figure 4 The room temperature tensile stress-strain curves of alloys 6 to 8 show that the Ti-Al-Mo-Cr-Nb titanium alloy of the present invention meets the following strength-plasticity matching requirements: when the tensile strength is at the level of 1150MPa, the elongation is not less than 13.5%; when the strength is at the level of 1200MPa, the elongation is not less than 10%; when the strength is at the level of 1350MPa, the elongation is not less than 6.5%. This shows that the Ti-Al-Mo-Cr-Nb titanium alloy of the present invention has excellent strength-plasticity matching and a wide performance control range.

[0062] The corrosion resistance of alloys 6 to 8 was further tested.

[0063] Table 3 shows the electrochemical corrosion test results of alloys 6 to 8 in 3.5wt.% NaCl solution. Their self-corrosion potentials are -0.422, -0.365 and -0.281 V vs. SCE, and their self-corrosion current densities are 2.738×10 -8 ,3.125×10 -8 and 3.671×10 -8 A / cm 2 , all exhibit excellent corrosion resistance.

[0064] Table 3: Electrochemical corrosion performance of alloys 6 to 8

[0065]

[0066] In summary, the Ti-Al-Mo-Cr-Nb titanium alloy of the present invention has excellent strength-ductility matching and corrosion resistance, and is expected to be used as a high-performance structural material in the fields of aerospace, marine ships, petrochemicals, etc.

Claims

1. A high-strength, corrosion-resistant Ti-Al-Mo-Cr-Nb titanium alloy, characterized in that: Calculated by weight percentage, its chemical composition is 3% ~ 4% Al, 6% ~ 7% Mo, 2% ~ 3% Cr, 2% ~ 5% Nb; the remainder is Ti and inevitable impurities.

2. The titanium alloy according to claim 1, characterized in that This titanium alloy has an equiaxed or dual-state structure.

3. A method for preparing a titanium alloy as claimed in claim 1 or 2, characterized in that: The steps include: The first step: batching, using block or granular high-purity metals of Ti, Al, Mo, Cr, and Nb as raw materials, accurately batching and mixing according to the required alloy composition; The second step: melting, using a vacuum magnetic levitation induction furnace to melt the alloy under argon protection to ensure uniform alloy composition; Step 3: Homogenization heat treatment: the smelted ingot is subjected to homogenization heat treatment, heated to 1100°C ~ 1150°C, kept warm for 2 hours, and then taken out and air-cooled; Step 4: β-opening forging, heating to 950°C ~ 1100°C, and β-opening forging the ingot; Step 5: Multi-pass rolling, in which the forging blank is rolled and formed in a temperature range of α+β phase, i.e., 780°C to 840°C; Step 6: Two-phase solid solution treatment: the rolled alloy is subjected to solid solution treatment, heated to 800°C ~ 830°C and maintained for 1 ~ 2 hours, and then taken out of the furnace and air cooled; Step 7: Aging treatment: The alloy after solution treatment is aged at 500°C ~ 600°C for 4 ~ 8 hours, and then air-cooled.

4. The method according to claim 3, characterized in that The vacuum suspension induction melting is repeated at least 3 times to make the alloy composition uniform.

5. The method according to claim 3, characterized in that The homogenization heat treatment temperature is 1100°C and the time is 2h.

6. The method according to claim 3, characterized in that The β-opening forging of the ingot refers to three-pass forging at 950°C ~1100°C, with the first pass temperature being 1100°C, the second pass temperature being 1000°C, and the third pass temperature being 950°C.

7. The method according to claim 3, characterized in that The forging billet is formed by multi-pass rolling in the α+β two-phase region, the multi-pass rolling temperature is 810°C, and the total deformation is 60%.

8. The method according to claim 3, characterized in that The solution treatment temperature is 820°C and the holding time is 1.5 hours.

9. The method according to claim 3, characterized in that The aging treatment temperature is 550°C and the holding time is 8 hours.